1995
DOI: 10.1136/gut.37.5.668
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the role of oral contraceptive agents in inflammatory bowel disease.

Abstract: Numerous epidemiological studies have been performed to determine factors that might contribute to the development of inflammatory bowel disease. Although the role oforal contraceptive agents in Crohn's disease (CD) and ulcerative colitis (UC) have been assessed, most studies were of small sample size and characterised by low statistical precision. A meta-analysis was performed to increase the statistical power and to investigate the association between the use of oral contraceptives and the development of CD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(56 citation statements)
references
References 25 publications
1
53
0
2
Order By: Relevance
“…Paradoxically, cigarette smoking is a risk factor for CD, but a protective factor for UC [12] . OC use may also play a role in the etiology of CD although, obviously, only in women [13,14] . Numerous dietary components may play a role in the etiology of IBD although these associations are less certain [16,17] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paradoxically, cigarette smoking is a risk factor for CD, but a protective factor for UC [12] . OC use may also play a role in the etiology of CD although, obviously, only in women [13,14] . Numerous dietary components may play a role in the etiology of IBD although these associations are less certain [16,17] .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous dietary components may play a role in the etiology of IBD although these associations are less certain [16,17] . Many investigators have identified associations between preceding infections and the development of IBD [13,[18][19][20]23,24] and some have identified associations between antibiotic use and development of IBD [23,24] . Many perinatal factors have been studied, but no consistent findings have been reported [21][22][23][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several publications have reported an increased risk of CD [97,139] or both CD and UC [140] among women using oral contraceptives. Similarly, a recent prospective cohort study has found that oral contraceptive use increased the risk of CD, but elevated risk of UC was only observed in women with a history of smoking [141].…”
Section: Medicationsmentioning
confidence: 99%
“…29 Oral contraceptives statistically significantly increased the risk for developing CD and appeared to increase the risk of UC. 30 The other important environmental factor playing on the development of IBD is diet control. The greatest association appears to be between increased sugar intake and developing IBD.…”
Section: Introductionmentioning
confidence: 99%